(untitled) (International Journal of Engineering and Computer Science, 2015)
Image denoising has been evolving as an essential exercise in medical imaging especially the Magnetic Resonance Imaging (MRI). The presence of noise in the biomedical images is one of the major challenge in image analysis and image processing. Denoising techniques are aimed at removing distortion or noise from the image while retaining the original quality of the image. Medical image obtained are often corrupted with noise. The MR images are processed to improve visual appearance to the viewers. Here we will discuss the multiresolution techniques such as scalar wavelet, multiwavelet and laplacian pyramid, Non local means (NLM) and compare their statistical parameters.